2020
DOI: 10.1016/j.jafrearsci.2019.103677
|View full text |Cite
|
Sign up to set email alerts
|

Petrological and geochemical study of Birimian ultramafic rocks within the West African Craton: Insights from Mako (Senegal) and Loraboué (Burkina Faso) lherzolite/harzburgite/wehrlite associations

Abstract: In Archean and Paleoproterozoic greenstone belts, ultrabasic (UB) rock occurrences are commonly found in close association within basic and differentiated magmatic series. In the Kedougou inlier (West African Craton), UB rocks are interbeded within the Birimian (2.1 Ga) Mako tholeiitic series (basalts, gabbros). UBs are typically lherzolite, harzburgite and wehrlite, characterized by their cumulative textures and relative proportions of chromite, olivine, clinopyroxene, amphibole ± orthopyroxene. Geochemical s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 97 publications
0
5
0
Order By: Relevance
“…These rocks, composed of gabbro dykes and amphibolite enclaves are characterized by a paragenesis mainly composed of green hornblende, plagioclase and clinopyroxene. This mineralogical composition is typical of mafic rocks described in the Birimian domain of the West African craton [10] [40] [41] [42].…”
Section: Discussionmentioning
confidence: 99%
“…These rocks, composed of gabbro dykes and amphibolite enclaves are characterized by a paragenesis mainly composed of green hornblende, plagioclase and clinopyroxene. This mineralogical composition is typical of mafic rocks described in the Birimian domain of the West African craton [10] [40] [41] [42].…”
Section: Discussionmentioning
confidence: 99%
“…-2200 Tholeiitic basalts are the oldest supracrustal rocks in the Baoulé-Mossi Domain and dominate the basal part of the lithostratigraphic record in each of the older belts of volcanic and volcano-sedimentary rocks (Fig. 1) across the region (Houndé-Boromo belt, Baratoux et al 2011;Nangodi belt, Sylvester and Attoh 1992; Sefwi belt, Hirdes et al 1993;Ashanti belt, Dampare et al 2008;Mako belt, Dioh 1986;Diallo 1994;Dia et al 1997;Abouchami et al 1990;Labou et al 2020). The timing of the onset of tholeiitic volcanism remains poorly constrained, but the presence of inherited zircons ca.…”
Section: The Geological History Of the Baoulé-mossi Domainmentioning
confidence: 99%
“…2200 Ma (De Kock et al 2011;Parra-Avila et al 2017). The geodynamic context of the juvenile tholeiitic oceanic crust remains uncertain, although plume-related oceanic plateau (Abouchami et al 1990;Boher et al 1992;, island arc (Sylvester and Attoh 1992;Baratoux et al 2011;Labou et al 2020), back-arc basin (Vidal and Alric 1994), and mid-ocean ridge (Pouclet et al 2006;Labou et al 2020) settings have been proposed.…”
Section: The Geological History Of the Baoulé-mossi Domainmentioning
confidence: 99%
“…The study area boundary chosen is the Ghanaian territory corresponding to the Precambrian West African Craton (Labou et al, 2020), shown in Fig. 1.…”
Section: Case Study Areamentioning
confidence: 99%